1998
DOI: 10.1046/j.1469-7580.1998.19230369.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of cytoplasm‐filled processes in cells of the intervertebral disc

Abstract: We examined cells from the nucleus pulposus and annulus fibrosus of adult bovine intervertebral discs, using confocal laser scanning microscopy on living unfixed tissue. These cells were visualised using chloromethyl fluorescein diacetate, a membrane-impermeant fluorescent dye. The organisation of cells from the outer annulus was also determined using confocal microscopy after fixation and staining the actin-filaments with FITC-phalloidin. We found that cellular processes were a dominant feature of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 20 publications
4
84
1
Order By: Relevance
“…The latter study used 18-24 month old bovine donors, while the former study did not report donor age. This is in contradiction with an earlier study where no evidence for NC was found in 18-24 month old cow tail IVDs [25]. Age separation of our dataset did not reveal a reduction in bT or bKrt19 in bovine donors aged above 24 or 48 months.…”
Section: Discussioncontrasting
confidence: 99%
“…The latter study used 18-24 month old bovine donors, while the former study did not report donor age. This is in contradiction with an earlier study where no evidence for NC was found in 18-24 month old cow tail IVDs [25]. Age separation of our dataset did not reveal a reduction in bT or bKrt19 in bovine donors aged above 24 or 48 months.…”
Section: Discussioncontrasting
confidence: 99%
“…Extensive sinuous cellular processes interwoven through annular collagenous fibres are evident in cells of the outer AF as well as strings of 10-12 cells interconnected by type VI collagen which is a prominent pericellular AF component particularly in the mid and inner AF [23,120]. This is consistent with type VI collagen's documented roles in the assembly of the basket-like chondron functional unit around cells of a chondrocytic background [46,107].…”
Section: The Pericellular Matrix Cell-matrix Interactions and Annulasupporting
confidence: 72%
“…A number of studies have demonstrated that the pericellular matrix of AF cells display a complex morphology [12,22,23,37,60]. Extensive sinuous cellular processes interwoven through annular collagenous fibres are evident in cells of the outer AF as well as strings of 10-12 cells interconnected by type VI collagen which is a prominent pericellular AF component particularly in the mid and inner AF [23,120].…”
Section: The Pericellular Matrix Cell-matrix Interactions and Annulamentioning
confidence: 99%
“…Unlike the nucleus, the outer annulus contains a relatively dense population of fibroblast-like cells (Figure 1) which tend to be elongated and aligned parallel to the layers or lamellae of collagen fibers [9]. Towards the inner annulus region, the cells are more chondrocytelike in appearances, and not necessarily aligned parallel to the collagen lamellae [17], these cells may appear in pairs or small clusters between the lamellae.…”
Section: Micro-anatomy Of Ivdsmentioning
confidence: 99%
“…It originates from the notochord and in the fetus and infants, it contains actively-dividing notochordal cells, which disappear at approximately eight years of age [8]. Interspersed at low density in the nucleus are chondrocyte-like nucleus pulposus cells [9], which may be present singly, or in pairs, and may frequently form small to large clusters, and occurrence of large clusters are considered to be a histological hallmark of intervertebral disc degeneration [10]. Along with the cells, the nucleus also contains type II collagen fibers which are randomly organized, and account for almost 20% of its dry weight [11].…”
Section: Micro-anatomy Of Ivdsmentioning
confidence: 99%